Designing science laboratories: learning environments, school architecture and teaching and learning models - Luísa Veloso; Marques, J. (Learning Environments Research, 2017)
This article on secondary schools science laboratories in Portugal focuses on how school space functions as a pedagogical and political instrument by contributing to shape the conditions for teaching and learning dynamics. The article places the impact of changes to school layouts within the larger context of a public school renovation programme, discussing how school space functions as a pedagogical and political instrument. The focus is on science laboratories as a particular learning environment for science education. The study, conducted between 2010 and 2011 in 13 renovated schools within the framework of the Portuguese Secondary School Modernisation Programme, drew on document analysis, interviews, pupil and teacher surveys and site-specific focus groups. One of the main findings is that teachers found that science laboratories were the most controversial and debated of all the renovated learning spaces. Considering that the science laboratory layout was intended to be universal across all schools, there was little intervention by the architects responsible for the renovation of the schools. Focusing on the analysis of the decision to change the science laboratory design within the aims of the education policy, this article discusses how teachers’ criticisms were a response to some of the educational policy goals underlying the renovation of school buildings and the potential impact on science education, namely, the relationship between flexibility of space organisation and pedagogical approaches.